The Concept of Children’s Character Education in the Family Environment According to Buya Hamka - Chairunnisa, Ema; M. Asyrakal; Haris, Abdul; Yazid, Syamsurizal (International Journal of Educational Research Excellence (IJERE), 2025)
This study aims to elaborate on the concept of children's character education within the family environment according to Buya Hamka. It employs a qualitative approach with a library research method. The data for this study were collected using documentation techniques, which involved reviewing and searching for information in the form of notes, books, journals, and other general scientific works. The analysis was conducted using content analysis techniques. The findings reveal that Buya Hamka emphasizes that the foundation of children's character education begins in the family environment. In this context, parents, specifically fathers and mothers, play a central role in shaping a child's character. The primary aspect of children's education starts and is implemented within the family setting. According to Buya Hamka, several methods can be applied to instill and shape a child’s character. These methods include exemplary behavior, advice, practice, habituation, discussion, and punishment. Additionally, three key steps for character building are identified. Firstly, parents, as the primary educators, must possess a pure and sincere spirit in nurturing their children’s character. Secondly, parents are obligated to provide advice to their children. Thirdly, parents should frequently engage their children in discussions.